Antineuroinflammatory therapy: potential treatment for autism spectrum disorder by inhibiting glial activation and restoring synaptic function. (29th August 2020) - Li, Yong-Jiang; Zhang, Xiaojie; Li, Ya-Min
Abstract: Autism spectrum disorder (ASD) is a neurodevelopmental disorder that is characterized by deficits in social interactions and perseverative and stereotypical behavior. Growing evidence points toward a critical role for synaptic dysfunction in the onset of ASD, and synaptic function is influenced by glial cells. Considering the evidence that neuroinflammation in ASD is mediated by glial cells, one hypothesis is that reactive glial cells, under inflammatory conditions, contribute to the loss of synaptic functions and trigger ASD. Ongoing pharmacological treatments for ASD, including oxytocin, vitamin D, sulforaphane, and resveratrol, are promising and are shown to lead to improvements in behavioral performance in ASD. More importantly, their pharmacological mechanisms are closely related to anti-inflammation and synaptic protection. We focus this review on the hypothesis that synaptic dysfunction caused by reactive glial cells would lead to ASD, and discuss the potentials of antineuroinflammatory therapy for ASD.